Circumstance [videorecording (DVD)] - Keshavarz, Maryam; Keshavarz, Maryam; Keshavarz, Maryam; Boosheri, Nikohl; Kazemy, Sarah, 1987-; Safai, Reza Sixo; Parsa, Soheil; Pakkho, Nasrin (Lionsgate, 2011)
A coming-of-age story set in the world of Iranian youth culture, filled with sex, drugs and defiance. A wealthy family struggles to contain their teenage daughter's growing sexual rebellion and her brother's dangerous obsession.